Immune dysregulation associated with co-occurring germline CBL and SH2B3 variants - Francesco Baccelli; Davide Leardini; Edoardo Muratore; Daria Messelodi; Salvatore Nicola Bertuccio; Maria Chiriaco; Caterina Cancrini; Francesca Conti; Fausto Castagnetti; Lucia Pedace; Andrea Pession; Ayami Yoshimi; et al. (Human Genomics, 2022)
Abstract Background CBL syndrome is a RASopathy caused by heterozygous germline mutations of the Casitas B-lineage lymphoma (CBL) gene. It is characterized by heterogeneous clinical phenotype, including developmental delay, facial dysmorphisms, cardiovascular malformations and an increased risk of cancer development, particularly juvenile myelomonocytic leukemia (JMML). Although the clinical phenotype has been progressively defined in recent years, immunological manifestations have not been well elucidated to date. Methods We studied the genetic, immunological, coagulative, and clinical profile of a family with CBL syndrome that came to our observation after the diagnosis of JMML, with homozygous CBL mutation, in one of the members. Results Variant analysis revealed the co-occurrence of CBL heterozygous mutation (c.1141 T > C) and SH2B3 mutation (c.1697G > A) in two other members. Patients carrying both mutations showed an ALPS-like phenotype characterized by lymphoproliferation, cytopenia, increased double-negative T-cells, impaired Fas-mediated lymphocyte apoptosis, altered cell death in PBMC and low TRECs expression. A coagulative work-up was also performed and showed the presence of subclinical coagulative alterations in patients carrying both mutations. Conclusion In the reported family, we described immune dysregulation, as part of the clinical spectrum of CBL mutation with the co-occurrence of SH2B3.